Assessing the Relationship Between Pre-Laying Morphometrics and Productivity Traits in Magelang Ducks for Sustainable Breeding - Dyah Maharani; Zakia Ulfah; Heru Sasongko (Caraka Tani: Journal of Sustainable Agriculture, 2026)
Traditional selection of Magelang ducks relies on visual assessments despite a lack of scientific validation. This study evaluated the relationships among pre-laying morphometrics and productivity, an approach previously unexplored in this population. A total of 107 female ducks (70 days old) were recorded and monitored individually for 366 days under identical conditions. Data were analyzed using descriptive statistics, Spearman’s correlation, and principal component analysis (PCA) to determine the independence of pre-laying morphometric and productivity traits. Productivity traits exhibited higher variability than pre-laying morphometrics, indicating that relatively uniform physical measurements do not reflect the wide range of production performance. Post-peak, extreme variability was driven by reproductive tract measurements, despite low variation in body weight, reflecting a physiological divergence that was hidden from external assessments. Spearman correlation revealed no significant relationship between pre-laying morphometrics and productivity. The mean age at molting was 398.65±29.31 days, occurring in 28.97% of ducks, and showed a weak positive correlation with production duration (235.25±39.27 days) and a significant, weak negative correlation with egg production (139.28±65.93 eggs). PCA identified 3 independent components: skeletal morphometrics (PC1), productivity (PC2), and body mass (PC3), which together accounted for 64.78% of the total variance. These findings confirm that visual selection for body size is ineffective for improving productivity. Researchers propose a two-stage selection strategy integrating skeletal screening with early performance recording and molecular markers. This framework enables farmers to identify elite layers and improve feed efficiency by culling unproductive, oversized ducks, thereby supporting sustainable breeding.